Vishnu with six arms -021 - Saurabh Saxena (2022)
Image courtesy : Saurabh Saxena - https://puratattva.in/ Here Vishnu can be seen with Shankha, Chakra, Padma, bow, and the other two hands are in the Abhaya and Varada mudra.